Design and Construction of Micro-hydro Model With Different Flowrate as a Learning Medium - Diki Ismail Permana; Dini Fauziah; Decy Nataliana (Department of Mechanical Engineering, Universitas Andalas, 2020)
Renewable energy generation such as hydropower, micro-hydro, and pico hydro are among the concerns of the government to reduce the greenhouse effect, gas emissions, and global warming and have set targets in 2025. Higher education institutions are expected to contribute to government development targets, one of which is by producing human resources, which is reliable, especially in the field of renewable energy and hydropower generation. So, we need innovative learning methods or media in the teaching and learning process. In this case, a set of demonstration tools in the form of a micro-hydro system model with varying parameters so that students can easily understand a course and could connect the theory with the real world/industry.